Initial Experience of 18F-FDG PET/MRI in Thymic Epithelial Tumors: Morphologic, Functional, and Metabolic Biomarkers. (January 2016) - Lee, Geewon; I, Hoseok; Kim, Seong-Jang; Pak, Kyoungjune; Cho, Jeong Su; Jeong, Yeon Joo; Lee, Chang Hun; Chang, Samuel
Abstract : Purpose: The aim of this study was to investigate the value of morphologic, functional, and metabolic biomarkers acquired concurrently at PET/MRI in patients with thymic epithelial tumors. Patients and Methods: During 1 year, 9 patients with suspected thymic epithelial tumors at contrast-enhanced chest CT were prospectively enrolled and underwent preoperative 18 F-FDG PET/MRI. Two chest radiologists prospectively reviewed the CT and MRI scans of PET/MRI in consensus, and 2 nuclear physicians reviewed the PET images. Visual assessment of the tumor morphology, functional biomarkers such as apparent diffusion coefficient from diffusion-weighted images, and metabolic biomarkers (including SUVmax, metabolic tumor volume, total lesion glycolysis, and heterogeneity index) were recorded. All patients underwent operation, and their pathologic reports served as the reference standard. Results: Thymic epithelial tumors were demonstrated in all 9 patients at pathologic examination. Tumor contour ( P = 0.012) and shape ( P = 0.033) had an association with the World Health Organization subtype, and the presence of septum ( P = 0.048) on MRI scans had an association with the Masaoka stage. In terms of functional and metabolic biomarkers, SUVmax (ρ = 0.683, P = 0.042) and SUV/apparent diffusion coefficient (ρ = 0.703, P = 0.035) correlated with the Masaoka stage. Metabolic tumor volume ( P = 0.024), heterogeneity index ( P = 0.024), and total lesion glycolysis ( P = 0.048) were useful for classification between low- and high-risk thymic epithelial tumors. Conclusions: Although limited by the small number of patients enrolled, morphologic, functional, and metabolic biomarkers derived from PET/MRI scans were useful for the stratification of thymic epithelial tumors.